Analisis Siyasah Qadha’iyyah Terhadap Kewenangan Mahkamah Konstitusi Dalam Diskualifikasi Calon Bupati Pesawaran Lampung - Aisyah Luna Marina; Maimun; M. Dani Fariz Amrullah D (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the authority of the Constitutional Court in disqualifying the Pesawaran Regent candidate based on Constitutional Court Decision Number 20/PHPU.BUP-XXIII/2025 and to examine such authority from the perspective of Siyasah Qadha’iyyah. This study employs a normative legal method using statutory, case, and conceptual approaches. Data were obtained through library research involving legislation, Constitutional Court decisions, legal literature, and relevant sources of Islamic law, which were analyzed qualitatively. The findings indicate that the disqualification of the Pesawaran Regent candidate in Constitutional Court Decision Number 20/PHPU.BUP-XXIII/2025 constitutes a juridical consequence of the Court’s assessment of candidacy requirements within the context of resolving the regional election results dispute. The Court’s consideration places the fulfillment of candidacy requirements as an aspect related to the validity of the electoral process and the legitimacy of the election results. From the perspective of Siyasah Qadha’iyyah, the exercise of such authority is consistent with the concept of wilayah al-qadha’, which encompasses the judicial function of resolving disputes, enforcing the law, protecting public rights, and realizing public welfare. Therefore, the disqualification may be understood as an exercise of judicial authority oriented toward justice, legal certainty, and public welfare.